2010
DOI: 10.4314/jasem.v11i2.55040
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Potential Health Hazards of Petrol Station Attendants in Owerri Nigeria

Abstract: Possible biochemical changes in hepatic and renal functions due to exposure of petrol vapour were assessed in twenty (20) petrol station attendants in Owerri, Imo State, Nigeria. A corresponding twenty healthy subjects who were not exposed to petrol or its vapour were used as controls. The results showed a significant increase in the (p<0.05) activities of alkaline phosphatase, alanine and aspartate aminotransferases for those exposed to petrol vapour from 6-10 years while the plasma bilirubin concentrations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
26
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 12 publications
15
26
5
Order By: Relevance
“…This work, as with other works 2,5 , also showed that the longer the subjects were exposed to the products, the more the effects on liver and more the severity ofthese effects. The findings of this study showed that there was increased prevalence of steatosis as well as the severity, as the exposure duration increased.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This work, as with other works 2,5 , also showed that the longer the subjects were exposed to the products, the more the effects on liver and more the severity ofthese effects. The findings of this study showed that there was increased prevalence of steatosis as well as the severity, as the exposure duration increased.…”
Section: Discussionsupporting
confidence: 82%
“…The exposure to petroleum products in Nigeria has many dimensions given the poverty pervading in the country that make people take jobs that expose them unduely to petroleum toxicants, stark ignorance of the exposed population and even majority of the health workers, the lack of occupational health laws and the inability to implement few existing industrial effluent regulations due to corruption. It has been documented in Nigeria, that petroleum products are used as therapeutic agents for the treatment of snake bites, arthritis, convulsion and gastro-intestinal disorders among others 2 . These taken together with increase in the prevalence of Liver diseases in Nigeria have made exposure to petroleum products an important area of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is in consonance with that of Nwanjo and Ojiako (2007) in petrol station workers and with that of Patrick-Iwuanyanwu et al (2011) in rats fed on kerosene and petrol contaminated diets. Gamma Glutamyl Transpeptidase (GGT) activity in the exposed group was higher by 99.12% relative to the control group, suggesting liver associated damage in the exposed group (Hyder et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…The alkaline phosphatase (ALP) activity was higher (p<0.05) in the depot workers which may imply alterations in the synthesis and transport of the enzyme following obstructive liver disease (Halim et al, 1997). This result agrees with that of Nwanjo and Ojiako (2007) in petrol station workers and that of Patrick-Iwuanyanwu et al (2011) but in rats fed on kerosene and petrol contaminated diets. The higher (p<0.05) aspartate amino transferase (AST) activity observed in the exposed group as against the control agrees with the report of Nwanjo and Ojiako (2007) for petrol station workers.…”
Section: Discussionsupporting
confidence: 75%